Usage and cost-effectiveness of anti-psychotics in psychiatry OPD among various clinical conditions: A prospective observational study in a tertiary care center - Reshabh Saini; Chandrasekaran Dhinakaran; Rohit Raina; Ramanathan Gandhibabu; Kathiresan Krishnasamy (Indian Journal of Psychiatry)
Background: Psychotropic medications are prescription drugs that are commonly used to control some symptoms associated with many different types of mental ill health. Although they cannot cure a patient illness, they can assist with the management of some extremely distressing symptoms and this in turn can facilitate individuals in leading a more fulfilled life. Aims and Objective: This study attempts to collect the demographic details of the outpatient in the psychiatric department and to describe the usage, prescribing trends and cost-effectiveness of antipsychotics in psychiatry OPD among various clinical conditions to older and younger patients with psychiatry disorders. Material and Methods: This study was a prospective observational study, conducted over a period of 6 months from November 2021 to April 2022 in the Department of Psychiatry, Chidambaram Government Medical College and Hospital, a 1400 bedded multi-specialty tertiary care teaching hospital, Tamil Nadu Dr. M.G.R. Medical University Chennai, Tamil Nadu. The recruitment of subjects was carried out with the help the physicians who had the knowledge of patient’s history and caregivers consenting to the study protocol and patients with case sheets carrying antipsychotics prescription. Observation and Results: A total number of 150 cases were enrolled in this study. All psychiatric OPD cases were studied and the results were taken. Based on the inclusion and exclusion criteria, 93 were the anti-psychotics prescribed cases and 57 were the non-anti-psychotics prescribed cases. Out of 93 patients, 69.89% (65 patients) were male and 30.10% (28 patients) were female. Out of non-psychotic 57 patients, 27 were male patients and 30 were female patients. Out of the 93 OPD patients, 40% of the patients have psychological based symptoms followed by 17% of patients have behavioral symptoms. 86.02% of patients received atypical antipsychotic medications in comparison with 36.55% of patients received the typical antipsychotic medications. Conclusion: In this study, we had observed the usage and types of anti-psychotic drugs to control and minimize the different psychotic symptoms among the OPD patients. Maximum antipsychotics studied were cost-effective and cheaper in Pradhan Mantri Bhartiya Janaushadhi Pariyojana (PMBJP) as compared to Intas, Torrent, Sun, Linux, Cipla, Abbott, Alkem, and Sanofi.